Substance misuse and primary health care among Indigenous Australians. Aboriginal and Torres Strait Islander Primary Health Care Review: Consultant Report No 7 - Gray, Dennis; Saggers, S.; Atkinson, D.; Strempel, Phillipa (2004)
The purpose of this review is to put a primary health care approach to substance misuse among Indigenous Australians into the context of: patterns of use; the health harms associated with substance misuse; the underlying causes of higher levels of use in Indigenous populations; and the broader range of Indigenous substance misuse interventions. Key findings of the review are presented below and references to the evidence base for those findings can be found in the main body of the text.